2011
DOI: 10.1007/s00776-011-0102-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of chronic musculoskeletal pain in Japan

Abstract: BackgroundThis cross-sectional study was conducted to obtain epidemiologic data on chronic musculoskeletal pain in the Japanese people, and with it a better understanding of the actual conditions and problems involved.MethodsA questionnaire covering basic information, chronic musculoskeletal pain, daily life, quality of life, and social loss was prepared and mailed to 11507 individuals aged 18 years or older. Subjects were selected randomly nationwide in accordance with the demographic composition of Japan.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
205
3
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(225 citation statements)
references
References 5 publications
13
205
3
4
Order By: Relevance
“…Pain amongst hospitalised patients is an under-treated and under-reported problem worldwide (Fairchild,2010;Nakamura et al, 2011;Robbins et al, 2012). All levels of healthcare providers need to be involved in order to manage pain successfully, especially nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Pain amongst hospitalised patients is an under-treated and under-reported problem worldwide (Fairchild,2010;Nakamura et al, 2011;Robbins et al, 2012). All levels of healthcare providers need to be involved in order to manage pain successfully, especially nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic musculoskeletal pain in the Japanese general population is at a frequency of 15.4%, and is highest in their 30s to 50s (Nakamura et al 2011). However, pain was reported to have increased at a frequency of 62% with a mean Numeric Rating Scale of 2.74, in the GEJE survivors (Yabuki et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As a part of this initiative, we undertook a "longitudinal investigation of chronic musculoskeletal pain" in 2010, supported by the Ministry of Health, Labour, and Welfare. The results so far [6][7][8] show that the prevalence of chronic musculoskeletal pain is 15.4%, and it is more common in females than in males. With regard to age, prevalence was highest in people aged 30-50 years.…”
Section: Introductionmentioning
confidence: 99%
“…These results from the cross-sectional analyses suggested that chronic musculoskeletal pain deprive one's ability to do social and daily life activities, and impair physical and mental performance. [6][7][8] Thus, chronic musculoskeletal pain is highly prevalent, resulting in a lower ADL and lower QOL. Previous studies reveal that musculoskeletal pain, especially low back pain, is the greatest cause of disability worldwide.…”
Section: Introductionmentioning
confidence: 99%